Robust convergence for inexact newton method - Argyros, Ioannis K; Magreñán, Á. Alberto (Iterative Methods and Their Dynamics with Applications: A Contemporary Study, 2020)
The main task this chapter is to use the iterative methods to find solutions x of the equation F(x) = 0, (7.1) where D : D ⊂ X → Y is a Fréchet-differentiable operator X, Y are Banach spaces and D ⊂ X. Many problems from Applied Sciences can be solved finding the solutions of equations in a form like (7.1) [9, 12, 14, 17, 18, 23, 25, 28-34].
Capítulo del libro "Iterative Methods and Their Dynamics with Applications: A Contemporary Study"
Keywords: computer science; mathematics & statistics; Scopus(2); WOS(2)